The Toxoplasma rhoptry protein ROP55 is a major virulence factor that prevents lytic host cell death - Margarida T. Grilo Ruivo; Ji-hun Shin; Todd Lenz; Stephanie Y. Matsuno; Katherine Olivia Yanes; Arnault Graindorge; Maguy Hamie; Laurence Berry-Sterkers; Mathieu Gissot; Hiba El Hajj; Karine G. Le Roch; Melissa B. Lodoen; et al. (Nature Communications)
Abstract Programmed-cell death is an antimicrobial defense mechanism that promotes clearance of intracellular pathogens. Toxoplasma counteracts host immune defenses by secreting effector proteins into host cells; however, how the parasite evades lytic cell death and the effectors involved remain poorly characterized. We identified ROP55, a rhoptry protein that promotes parasite survival by preventing lytic cell death in absence of IFN-γ stimulation. RNA-Seq analysis revealed that ROP55 acts as a repressor of host pro-inflammatory responses. In THP-1 monocytes ΔROP55 infection increased NF-κB p65 nuclear translocation, IL-1β production, and GSDMD cleavage compared to wild type or complemented parasites. ΔROP55 infection also induced RIPK3-dependent necroptosis in human and mouse primary macrophages. Moreover, ΔROP55 parasites were significantly impaired in virulence in female mice and prevented NF-κB activation and parasite clearance in mBMDM. These findings place ROP55 as a major virulence factor, dampening lytic cell death and enabling Toxoplasma to evade clearance from infected cells.